2014
DOI: 10.4317/jced.51355
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of salivary alpha amylase as a biomarker of chronic stress and stress related oral mucosal changes - a pilot study

Abstract: Introduction: Salivary biomarkers are suggested to provide a reliable, noninvasive and objective measurement of chronic psychosocial stress and helps in assessment of pivotal role of stress in causation or precipitation of multitude of health problems. Objectives: To evaluate the usefulness of salivary alpha amylase activity as an objective indicator of chronic stress and to find out any correlation between stress- related mucosal complaints and its levels. Study Design: Study was conducted among 50 subjects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 32 publications
1
38
0
7
Order By: Relevance
“…The level of salivary alpha-amylase increases in patients with chronic psychosocial stress, but may not be an indicator to suggest the development of stress related to changes in oral mucosa. The levels of salivary alpha-amylase reflect the activity of the sympathetic nervous system [12] and can be used as a stress biomarker since physiological and psychological changes cause an increase in their levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of salivary alpha-amylase increases in patients with chronic psychosocial stress, but may not be an indicator to suggest the development of stress related to changes in oral mucosa. The levels of salivary alpha-amylase reflect the activity of the sympathetic nervous system [12] and can be used as a stress biomarker since physiological and psychological changes cause an increase in their levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that any psychological or physiological change is followed by an increase of these stress biomarkers [13,14]. In addition, salivary biomarkers have gained popularity because they are reliable, easy to use, non-invasive and of rapid collection, compared to samples such as blood and urine [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva sampling is a noninvasive, easy, and stress-free procedure [53], so levels of salivary cortisol have previously been used to assess endocrine activity [54,55]. However, since α-amylase responds more quickly and sensitively to psychological stress than cortisol [56], it has been widely used to quantify this [35,53,[56][57][58][59][60][61].…”
Section: Psychological Assessmentmentioning
confidence: 99%
“…There were no patients with anxiety disorders, depressive episodes, or hyperlipidemia in group 3, even though many studies have referred to high saliva (20,21). In all groups of diseases, the patients with abdominal and pelvic pain made up the highest percentage (16.0%).…”
Section: Discussionmentioning
confidence: 95%